Problems of moral development of elementary school age children in the kriyan ngadiluwih kediri localization area - Dwinata, Anggara; Siswanto, M Bambang Edi; Raharja, Hawwin Fitra (Universitas Nusantara PGRI Kediri, 2023)
This study aims to find out in general the process of inculcating morals in elementary school age children in the Kriyan localization area, Ngadiluwih, Kediri. The type of research used is a qualitative study with a case study research design. The sample in this study was six resource persons consisting of three parents and three students. Research data were collected through interviews, observation, and document analysis. Based on the results of study, it is shown that parents instill moral values ​​in their children from the age of 5-10 years with simple activities such as studying hard, not lying, not swearing, dressing neatly, speaking well, and learning to respect each other. By inculcating morals from elementary school age, it will make children easy to be accepted in society.